The immateriality of the human mind, the semantics of analogy, and the conceivability of God - Klima, Gyula; Hall, Alexander W. (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2011)
The Immateriality of the Human Mind, the Semantics of Analogy, and the Conceivability of God brings together the work of experts in the field of medieval philosophy to consider the nature of God and the soul, what can be known of the divine essence and th
Description based on print version record.
Keywords: Theology, Doctrinal; God -- Proof; Intellect; Philosophy, Medieval; RELIGION / General; Electronic books